2016
DOI: 10.1590/1516-4446-2016-1910
|View full text |Cite
|
Sign up to set email alerts
|

Shortened telomere length in bipolar disorder: a comparison of the early and late stages of disease

Abstract: Objective: Bipolar disorder (BD) has been associated with increased rates of age-related diseases, such as type II diabetes, metabolic syndrome, osteoporosis, and cardiovascular disorders. Several biological findings have been associated with age-related disorders, including increased oxidative stress, inflammation, and telomere shortening. The objective of this study was to compare telomere length among participants with BD at early and late stages and age-and gender-matched healthy controls. Methods: Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 49 publications
(58 reference statements)
4
27
1
1
Order By: Relevance
“…1 Their results support the theory of accelerated aging in BD, even present since the early stages of the disease.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…1 Their results support the theory of accelerated aging in BD, even present since the early stages of the disease.…”
supporting
confidence: 66%
“…The authors reported that all but three patients were on polytherapy, but due to the sample size they could not explore LTL and type/number of medications. 1 Second, is this ''propensity'' for shorter LTL at early stages of BD genetically predetermined? The family history of patients is not mentioned in this article.…”
mentioning
confidence: 99%
“…[43][44][45] Therefore, it is necessary to study aging during CIK cell proliferation and self-renewal by monitoring the activity or magnitude of telomeres on day 0, 7, and day 14. [46][47][48][49] Although there is no significant evidence to suggest the correlation between the efficiency of tumor immunotherapy and the age of CIK cells, understanding of this correlation is important for the effective development of CIK cell-based immunotherapy.…”
Section: The Aging Of Cik Cellsmentioning
confidence: 99%
“…Faster shortening of telomeres has been found after life stress (Epel et al, 2004), exposure to violence during childhood (Shalev et al, 2013), experiencing highly disadvantaged environments (Mitchell et al, 2014) and early life adversity (Ridout et al, 2018). Short TL in psychiatry has been linked primarily to patients suffering from major depressive disorder (Hartmann, Boehner, Groenen, & Kalb, 2010;Lung, Chen, & Shu, 2007;Monroy-Jaramillo, Dyukova, & Walss-Bass, 2017;Ridout, Ridout, Price, Sen, & Tyrka, 2016;Schutte & Malouff, 2015), post-traumatic disorder (Lindqvist et al, 2015;Shalev et al, 2013), anxiety disorders (Monroy-Jaramillo et al, 2017;Shalev et al, 2013) and bipolar disorder (Barbé-Tuana et al, 2016;Lima et al, 2015). However, not all patients have shortened TL, and evidence suggests that TL may actually be marking the effects of specific environmental risk factors for psychiatric disorders, or the severity of specific cognitive biases or symptoms, rather than representing a definitive case/control predictor (Elvsåshagen et al, 2011;Powell, Dima, Frangou, & Breen, 2018;Vincent et al, 2017).…”
Section: Introductionmentioning
confidence: 99%